From infancy to adolescence: growing up in poverty - Dornan, Paul (2014)
The Young Lives study is following the lives of 12,000 children over 15 years in Ethiopia, Andhra Pradesh in India,1 Peru and Vietnam. It includes an Older Cohort of children born in 1994–95 and a Younger Cohort born in 2001–02 (see Figure 1). By collecting information in low- and middle-income countries at different stages of national development, we hope to tell a broader story of what matters for children and when. Longitudinal analysis enables us to identify how and why factors early in life shape children’s later outcomes, and how inequalities emerge, giving insights for key entry points for policies to support children’s development and well-being at different ages. The design of Young Lives enables us also to consider differences in the outcomes of children at the age of 12, comparing the Older and Younger Cohorts in order to identify change between 2006 and 2013.